2014
DOI: 10.1039/c3cc48309f
|View full text |Cite
|
Sign up to set email alerts
|

A new mussel-inspired polydopamine phototransistor with high photosensitivity: signal amplification and light-controlled switching properties

Abstract: A polydopamine (PDA) thin film with a dense and conformal surface was prepared under optimized deposition conditions using O2 gas as an oxygen source. The PDA-based organic phototransistors exhibited high photosensitivity and photo-controlled switching properties under light illumination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 27 publications
1
45
0
Order By: Relevance
“…in light emitting diodes and fi eld effect transistors. [16][17][18][19][20][21] Recently, we demonstrated that polydopamine (pDA) (or dopamine-melanin), a versatile eumelanin-type polymer with strong adhesion properties, [22][23][24][25][26] displays semiconductor-like properties that can be modifi ed by chemical manipulation. In particular, covalent incorporation of aromatic amines into the pDA structure during polymerization induced a marked shift of the fl at band voltage tuning its intrinsic semiconductor properties to n-type behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…in light emitting diodes and fi eld effect transistors. [16][17][18][19][20][21] Recently, we demonstrated that polydopamine (pDA) (or dopamine-melanin), a versatile eumelanin-type polymer with strong adhesion properties, [22][23][24][25][26] displays semiconductor-like properties that can be modifi ed by chemical manipulation. In particular, covalent incorporation of aromatic amines into the pDA structure during polymerization induced a marked shift of the fl at band voltage tuning its intrinsic semiconductor properties to n-type behavior.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning in this regard a paper reporting insertion of a p-doped pDA thin fi lm with a dense and conformal surface as an optically active channel in OTFT transistors to implement an organic phototransistor with high photosensitivity and photo-controlled switching properties. [ 21 ] An attractive bio-inspired strategy to improve the light response of pDA is based on the incorporation within the pDA scaffold of pheomelanin-type benzothiazine and benzothiazole units that could serve as photosensitizing components. Although pheomelanins exhibit intrinsically poor emission properties with a complex dependence of quantum yields on the excitation energy, they can easily eject electrons upon photoexcitation, as evidenced by free electron laser-photoelectron emission microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the deposition, each piece of substrates was chemically cleaned using the piranha cleaning procedure. 23 …”
Section: Pre-deposition Cleaning Of Substratesmentioning
confidence: 97%
“…The surface profi le rootmean-square roughness of the entire area (250 nm × 250 nm) was determined to be 0.46 ± 0.09 nm, comparable with that of dopamine-melanin thin fi lms formed on solid substrates (0.31 nm). [ 18 ] The Fourier transform infrared (FTIR) spectrum of the nanofi lm showed characteristic vibrations of dopamine-melanin: 3307 ( ν (N H), ν (O H)); 3045, 2925 ( ν (C H)); 1597,1490 ( ν ring (C C), ν ring (C N));1433 ( ν ring (C C)); and 1298 cm −1 ( ν ring (CNC)) (Figure 1 d). These signals were consistent with the previous results for dopamine-melanin nanofi lms formed directly on substrate surface, [ 19 ] indicating that the melanin nanofi lms formed via a similar mechanism.…”
Section: Doi: 101002/admi201500203mentioning
confidence: 97%